RANCANGAN AUTOMATIC SWITCHING SERIAL OUTPUT DATA RADAR DI JAKARTA AIR TRAFFIC SERVICES CENTRE (JATSC) BERBASIS MIKROKONTROLER ARDUINO - Antarizkia Nur Fitri Ramadhani; Achmad Setiyo Prabowo; Sudrajat (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Jakarta Air Traffic Services Center (JATSC) is able to serve approximately 5000 flights / day at Soekarno-Hatta International Airport. With the large number of flights a day, Soekarno-Hatta International Airport requires uninterrupted Radio Detection and Ranging (Radar) data. JATSC has used two Fiber Optic (FO) lines as transmission media from the radar site to the Main Equipment Room (MER). At present, JATSC still uses manual switching for the two FO lines which will later be connected to the automation system.